Effect of Increased Blood Flow Rate on Hemodialysis Tolerability and Achieved Urea Reduction Ratio. Issue 5 (4th July 2018) - Ryan, Peter; Le Mesurier, Lauren; Adams, Kelly; Choi, Peter; Chacko, Bobby
Abstract: Long‐term hemodialysis (HD) imposes a significant burden on the quality of life of end‐stage kidney disease patients. Optimizing dialysis dose is an important consideration in this population; however, evidence exists that suggests that attainment of population dialysis targets is associated with increased intradialytic complications. In this prospective, before‐after study, the blood flow rate (BFR) of 63 maintenance HD patients was increased by 100 mL/min to a maximum BFR of 400 mL/min to determine the impact on patient tolerability and urea reduction ratio (URR) of an increased BFR. Tolerability was assessed by time to recovery (TTR) after dialysis, a validated measure of patient tolerability, and intradialytic complications. Median pre‐increase BFR was 252 mL/min compared to 349 mL/min post‐increase. Mean TTR decreased from 4.67 h to 4.03 h ( P = 0.688). No association was observed between percentage change in BFR (R2 = 0.0) or post‐increase BFR (R2 = 0.0) and absolute change in TTR. A significant, positive association was observed between both the absolute and relative changes to BFR and the achieved URR. We found no evidence that increasing BFR by 100 mL/min diminishes patient tolerability.